IMPLEMENTING DISCOVERY LEARNING METHOD TO INCREASE STUDENTS’ SCIENCE LEARNING OUTCOMES AT GRADE IV SDN ENDE 12 KECAMATAN ENDE UTARA, KABUPATEN ENDE - Yuliana Yenita Mete; Ainun Jariyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The purpose of this study was to improve students’ learning outcomes through the implementation of discovery learning method. This study utilized a classroom action research (CAR) model consisting of two cycles. Each cycle was conducted in one meeting which involving several stages, namely the planning stage, the action stage, the observation stage, and the reflection stage. The subjects of this study were 27 students at grade IV SD Ende 12 Kecamatan Ende Utara, Kabupaten Ende, consisting of 15 boys and 12 girls. Data were collected by administering a science learning outcome test in each cycle. In addition, observation sheets were also utilized to measure students’ participation during teaching and learning activities. The results of this study indicated that discovery learning method improved the students’ learning outcomes at grade IV SD Ende 12. This was seen from the improvement of the students’ learning outcomes from cycle I and II. The average science learning outcomes for Types of Soil at the end of cycle I was 65.18 and increased to 88.51 in cycle II.